Isolation of New Gravitropic Mutants under Hypergravity Conditions - Mori, Akiko; Toyota, Masatsugu; Shimada, Masayoshi; Mekata, Mika; Kurata, Tetsuya; Tasaka, Masao; Morita, Miyo T. (Frontiers in Plant Science, 2016)
Forward genetics is a powerful approach used to link genotypes and phenotypes, and mutant screening/analysis has provided deep insights into many aspects of plant physiology. Gravitropism is a tropistic response in plants, in which hypocotyls and stems sense the direction of gravity and grow upwards. Previous studies of gravitropic mutants have suggested that shoot endodermal cells in Arabidopsis stems and hypocotyls are capable of sensing gravity (i.e., statocytes). In the present study, we report a new screening system using hypergravity conditions to isolate enhancers of gravitropism mutants, and we also describe a rapid and efficient genome mapping method, using Next-Generation Sequencing (NGS) and Single Nucleotide Polymorphism (SNP)-based markers. Using the endodermal-amyloplast less 1 (eal1) mutant, which exhibits defective development of endodermal cells and gravitropism, we found that hypergravity (10 g) restored the reduced gravity responsiveness in eal1 hypocotyls and could, therefore, be used to obtain mutants with further reduction in gravitropism in the eal1 background. Using the new screening system, we successfully isolated six ene (enhancer of eal1) mutants that exhibited little or no gravitropism under hypergravity conditions, and using NGS and map-based cloning with SNP markers, we narrowed down the potential causative genes, which revealed a new genetic network for shoot gravitropism in Arabidopsis.